PENGARUH KEIKUTSERTAAN SISWA DALAM EKSTRAKURIKULER ROHIS TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN AKIDAH AKHLAK - Ferdiansyah, Akmal; Triwoelandari, Retno; Gustiawati, Syariah (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2019)
Motivation is really needed for students to make them enthusiastic and focused in learning. Extracurricular can develop the potential, talents, interests, abilities of students to become better individuals than before. It is hoped that students who take extracurricular activities can become students who have more and more developed competencies than before. This study aims to determine the learning motivation of students who take part in Rohis extracurricular activities at MA Negeri 1 Bogor City. The approach used in this research is quantitative, using ex-post facto methods. Data collection methods used were questionnaires and analysis techniques used were product moment correlation. The results showed that; there is a significant influence between the participation of students in the spiritual extracurricular on the motivation to learn morality by 0.504. Thus, to increase student motivation can be done with a variety of things but by following the spiritual extracurricular in addition to increasing motivation, students can also develop their potential in various aspects and make themselves have many advantages.